PENGARUH DEBT TO ASSET RATIO (DAR), RETURN ON ASSET (ROA), DAN SIZE TERHADAP NILAI PERUSAHAAN (PBV) (Studi Kasus Pada Perusahaan Sektor Industrials Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022) - Asmin, Erny Amriani; Kartini, Tini; Alvianingsih, Anggita (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This research aims to determine the influence of Debt to Asset Ratio (DAR), Return on Assets (ROA), and size on company value (PBV), partially and simultaneously. Data processing in this research uses quantitative data analysis and uses SPSS 25 (Statistical Package for Social Science) software. The sample in this research is industrial sector companies listed on the Indonesia Stock Exchange, totaling 31 companies during the 2020-2022 period. The research results show that Debt to Asset Ratio (DAR), Return On Assets (ROA), and Size together or simultaneously influence company value (PBV). Debt to Asset Ratio (DAR) partially has a positive and significant effect on Company Value (PBV). Return on Assets (ROA) partially has a positive and significant effect on Company Value (PBV). Size has a negative and significant effect on Company Value (PBV). And the Return On Assets (ROA) variable is the dominant variable.